Review of Odontochrydium Brauns (Hymenoptera, Chrysididae) with description of two species from the Palaearctic and Oriental regions - Rosa, Paolo (Zootaxa, 2018)
The genus Odontochrydium Brauns, 1928, previously known only from the Afrotropical Region, is recorded from the Palaearctic Region (Saudi Arabia) and the Oriental Region (Southern India) for the first time. Odontochrydium bicristatum sp. nov. from Kenya and Saudi Arabia and O. xui sp. nov. from India are described. Pictures and a key to the species of this genus are given.